KEBUTUHAN AKAN PRESTASI DAN KESIAPAN INSTRUMENTASI SEBAGAI PREDIKTOR INTENSI KEWIRAUSAHAAN MAHASISWA (STUDI PADA MAHASISWA PEMINATAN KEWIRAUSAHAAN PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS TARUMANAGARA) - Hendra Wiyanto (Jurnal Manajemen., 2014)
This study examined the influence of the need for achievement, and readiness instrumentation in influencing entrepreneurial intentions of students. The research employed quantitative approach. The population of the research was students of the management study program, the Economics Faculty, Tarumanagara University that were registered in the odd semester 2013/2014 and had taken entrepreneurship course. Samples involved in the research used purposive sampling. The data collection was conducted using the inquiry method, while multiple linear regression analysis was employed to analyze the data. The finding of the research indicates that (1) the need for achievement positively affects the entrepreneurial intention of students (2) the result of readiness instrumentation affects significantly the entrepreneurial intention of students, (3) the need for achievement and readiness instrumentation jointly influence the entrepreneurial intentions of students. The finding of the research implies that what has been indicated by a theory that predicts the result of the need for achievement, and readiness instrumentation that is assumed to affect the interest to make business through entrepreneurial intention prevail completely for the students of the entrepreneurship course of the management study program at the Economics Faculty, Tarumanagara University. Based on the finding of the research, it is suggested that efforts to improve the entrepreneurial intention of students can be conducted by improving their need for achievement, and readiness instrumentation. This will need a curriculum design of entrepreneurship course that can create or improve the students’ need for achievement since it will have effect on the improvement of entrepreneurial intention in making business.